Reproductive aspects of dendropsophus sanborni (anura, hylidae) in northeastern Argentina - Curi, Lucila Marilén (2014)
Fil: Curi, Lucila Marilén. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas, Naturales y Agrimensura. Departamento de Biología; Argentina.